It's agony for us as well: Neonatal nurses reflect on iatrogenic pain. (March 2016) - Green, Janet; Darbyshire, Philip; Adams, Anne; Jackson, Debra
Background: Improved techniques and life sustaining technology in the neonatal intensive care unit have resulted in an increased probability of survival for extremely premature babies. The by-product of the aggressive treatment is iatrogenic pain, and this infliction of pain can be a cause of suffering and distress for both baby and nurse. Research question: The research sought to explore the caregiving dilemmas of neonatal nurses when caring for extremely premature babies. This article aims to explore the issues arising for neonatal nurses when they inflict iatrogenic pain on the most vulnerable of human beings – babies ≤24 weeks gestation. Participants: Data were collected via a questionnaire to Australian neonatal nurses and semi-structured interviews with 24 neonatal nurses in New South Wales, Australia. Ethical consideration: Ethical processes and procedures set out by the ethics committee have been adhered to by the researchers. Findings: A qualitative approach was used to analyse the data. The theme 'inflicting pain' comprised three sub-themes: 'when caring and torture are the same thing', 'why are we doing this!' and 'comfort for baby and nurse'. The results show that the neonatal nurses were passionate about the need for appropriate pain relief for extremely premature babies. Conclusion: The neonatal nurses experienced a profound sense of distress manifested as existential suffering when they inflicted pain on extremely premature babies. Inflicting pain rather than relieving it can leave the nurses questioning their role as compassionate healthcare professionals.